2013
DOI: 10.1177/0040517513490063
|View full text |Cite
|
Sign up to set email alerts
|

Waterproof and durable screen printed silver conductive tracks on textiles

Abstract: Conductive textiles are fabrics that include conductive yarns woven into or conductive tracks printed on to the textiles. Conductive textiles have attracted significant attention, since they are fundamental for the integration of electronic functions to achieve wearable devices. Screen printing is a well-established and cost-effective fabrication method; it enables a versatile layout of conductive tracks. The limitation of the current screen-printed conductive textiles is low durability to weathering, abrasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 15 publications
0
83
0
Order By: Relevance
“…To reduce the variations in thickness of the printed layers an extra layer could be printed first to smooth the woven fabric surface, as used by Yang et al [17]. …”
Section: ) Results and Discussionmentioning
confidence: 99%
“…To reduce the variations in thickness of the printed layers an extra layer could be printed first to smooth the woven fabric surface, as used by Yang et al [17]. …”
Section: ) Results and Discussionmentioning
confidence: 99%
“…The inherent surface roughness and pilosity of textiles also presents a significant challenge. Textiles can be pre-coated with a smooth film or a printed polyurethane waterproof interface layer has been developed in our research group for planarising the textile surface [16]. The curing temperature limitation of the polyester cotton means the films resistivity will be high (see Fig.…”
Section: Thermoelectric Thick Films On Textile Substratementioning
confidence: 99%
“…This makes it extremely difficult to manufacture electronics directly onto textiles. An additional coating on top of the fabric can be used to planarise the surface and these can be laminated or printed to the textile [13], [14]. Electronic components and interconnects can be incorporated onto this surface.…”
Section: Wearable Electronicsmentioning
confidence: 99%
“…Washing is a very harsh environment for wearable e-textiles causing mechanical strain, abrasion as well as exposure to water and detergents. Although the research into waterproof material as the encapsulation has been reported [13], washability of wearable electronics is still a key challenge to resolve.…”
Section: Wearable Electronicsmentioning
confidence: 99%